Lemierre Syndrome: An Overlooked Diagnosis in Otherwise Healthy Patients - Costa,Patrícia (2021)
Abstract Lemierre Syndrome is a severe complication of an otorhinolaryngologic infection, resulting in septic thrombophlebitis, bacteriemia and septic emboli, most often in young and previously healthy patients. We present a case of a 24-year-old female patient, that develops an episode of syncope and multiorganic dysfunction, two days after the diagnosis of acute tonsillopharyngitis treated with intramuscular penicillin and anti-inflammatory drugs. Due to worsening of the clinical status, a computed tomography was performed and radiological findings were in keeping with Lemierre Syndrome. The continuous worsening of respiratory and cardiovascular dysfunction led to intensive care unit admission where the patient was submitted to extra-corporeal membrane oxygenation support. Despite being a rare entity, Lemierre Syndrome is potentially life-threatening, therefore it should be recognized as soon as possible. Given its unspecific clinical presentation, a high index of suspicion and radiological evaluation with computed tomography are needed to establish the diagnosis.